2023
DOI: 10.3839/jabc.2023.065
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant and immune enhancement effects of Artemisia argyi H. fermented with lactic acid bacteria

Ji Yun Lee,
Ji Hyun Kim,
Ji Myung Choi
et al.

Abstract: This study investigated the antioxidant and immune enhancement activities of Artemisia argyi H. fermented by Lactobacillus plantarum. The fermented A. argyi H. ethanol extract increased scavenging activities of 1,1-diphenyl-2picrylhydrazyl (DPPH), 2,2'-azinobis-(3-ethylbenzothiazoline-6sulfonic acid) (ABTS + ), hydroxyl (•OH), and superoxide (O 2 -) radicals. Particularly, the ethanol extract of fermented A. argyi H. exhibited higher •OH and O 2 radical scavenging activities, compared with DPPH and ABTS + rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Our previous study reported that the fermented A. argyi H. with L. plantarum (FAA) contained a more bioactive component, jaceosidin, than non-fermented A. argyi H. with L. plantarum [23]. Furthermore, the immune enhancement effect and antioxidant activity of FAA were demonstrated [24]. These findings suggested its potential as a functional material for preventing and improving inflammatory responses.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our previous study reported that the fermented A. argyi H. with L. plantarum (FAA) contained a more bioactive component, jaceosidin, than non-fermented A. argyi H. with L. plantarum [23]. Furthermore, the immune enhancement effect and antioxidant activity of FAA were demonstrated [24]. These findings suggested its potential as a functional material for preventing and improving inflammatory responses.…”
Section: Introductionmentioning
confidence: 91%
“…A. argyi H. was supplied from the farming association of A. argyi H. in Namhae [23], and FAA was processed by the following procedures [24]. The A. argyi H. leaves were steamed at 100 • C for 5 min, then crushed in malt extract broth.…”
Section: Sample Preparationmentioning
confidence: 99%